"Now I keep my feet on the ground. Earlier, I was arrogant and felt too big for my boots." Perspectives of people with cancer and oncology nurses on the psychological empowerment process. (December 2020) - Hi̇çdurmaz, Duygu; Üzar-Özçetin, Yeter Sinem
Abstract: Purpose: A deeper understanding of the psychological empowerment process of people with cancer can provide improved practical strategies for healthcare professionals to assist the patients in maintaining hope and overcoming difficulties. This study aimed to describe, interpret, and understand the phenomenon of the psychological empowerment process related to cancer from the perspectives of people with cancer and oncology nurses. Method: The present descriptive qualitative design study was conducted between May 2017 and August 2017, in the oncology clinics of a university hospital. A purposive sampling method was applied to recruit adult patients diagnosed with different types and stages of cancer. The semi-structured interviews were conducted with thirteen patients and sixteen nurses. The data were transcribed, themes were identified, and the COREQ (Consolidated criteria for Reporting Qualitative Research) Checklist was used to ensure quality reporting in this study. Results: This study categorized quotes of patients and nurses into four main themes including "gains and losses", "meaning of life", "presence and contact", and "need to be understood". Both patients and nurses shared similar thoughts toward the factors associated with the psychological empowerment process during the cancer experience. Conclusion: Being aware of patients' requirements along with raising effective support to help them grow stronger while preventing the disparity between the support that patients require and receive are some of the aspects that need to be considered for the provision and organization of healthcare services related to the psychological empowerment of people with cancer. Highlights: The findings underscore the process of psychological empowerment in one's life in the cancer experience. The findings emphasized that positive adaptation may be possible by managing relations and accepting changes. It is evident that meaning finding via confronting the cancer and re-adapting to daily life are essential components. The competency of healthcare professionals in psychosocial care is an important requirement worth to be improved.